2016
DOI: 10.3390/ma9010058
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Surfactant Concentrations on the Properties of Mesoporous Bioactive Glass

Abstract: Bioactive glass (BG), a potential biomaterial, has received increasing attention since the discovery of its superior bioactivity. One of the main research objectives is to improve the bioactive property of BGs; therefore, surfactant-derived mesoporous bioactive glasses (MBGs) were developed to provide a high specific surface area for achieving higher bioactivity. In this study, various concentrations of typical triblock F127 surfactant were used to manipulate the morphology, specific surface area, and bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Next, Figure 8 b shows the comparison between specific surface areas and bioactivity of all BG powders. The graph shows that BG powders with higher specific surface area correspond to the higher value of I 1 /I 2 (i.e., greater HA formation), which agree well with previous results on MBG studies [ 13 , 30 , 31 ]. Finally, to the best of our knowledge, the surface area achieved in this study of 232.7 m 2 /g exceeds the P123-treated MBG particles of 165.0 m 2 /g [ 32 ] and thus becomes the highest specific surface area reported for SP-derived MBG powders to date.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Next, Figure 8 b shows the comparison between specific surface areas and bioactivity of all BG powders. The graph shows that BG powders with higher specific surface area correspond to the higher value of I 1 /I 2 (i.e., greater HA formation), which agree well with previous results on MBG studies [ 13 , 30 , 31 ]. Finally, to the best of our knowledge, the surface area achieved in this study of 232.7 m 2 /g exceeds the P123-treated MBG particles of 165.0 m 2 /g [ 32 ] and thus becomes the highest specific surface area reported for SP-derived MBG powders to date.…”
Section: Discussionsupporting
confidence: 91%
“…However, the use of surfactants may cause problems such as micelle aggregation and carbon contamination. The micelle aggregation will produce particles with a wrinkled surface and hence reduce the porosity and surface area of the resulting specimen [ 13 ]. In addition, carbon contamination will inhibit the formation of HA.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported that highly porous and small‐sized materials improve bioactivity and specific surface area . Particle shape and size also play an essential factor in cellular attachment and its responses as a consequence of the biological activities.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the size of crystallites in the sample with surfactin after 24 h of ageing is significantly lower than in the control sample ( Figure 7 A). This results from oval and spherical depletions on the calcite crystal surface [ 52 ]. On the calcite surface, the edges are more rounded and truncated, indicating the presence of micelles on the edges of the crystals.…”
Section: Resultsmentioning
confidence: 99%